Effect of Graphite on the Microstructure and Density of Aluminium Composite AA6061 Using Hot Press Forging - Shamsul, Fatin Shamila; Mustapa, Mohammad Sukri (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The growing demand for aluminium has resulted in an increase in scrap waste, necessitating the development of efficient recycling methods. This research investigates the application of hot press forging in the production of aluminium AA6061 composites reinforced with graphite particles, aiming to improve physical properties while considering environmental and economic factors. Recycled aluminium AA6061 chips were processed with different graphite contents: Al+0% Graphite, Al+2.5% Graphite, Al+5% Graphite, Al+7.5% Graphite, Al+10% Graphite, and Al+12.5% Graphite. The specimens underwent compaction at 1000 psi and were subjected to hot press forging at 530°C with a pressure of 35 tonnes. The composites were analysed for density, porosity, and microstructure utilizing a Dino-Lite microscope. The results indicated that an increase in graphite content led to a reduction in density and a refinement of grain size, with Al+10% Graphite exhibiting the smallest grain size of 1.28 mm and the lowest porosity at 98.98%. At Al+12.5% Graphite, minor increases in porosity and grain size suggested matrix saturation. The findings indicate that different levels of graphite content have a substantial impact on the density, porosity, and microstructure of aluminium AA6061 composites. This study demonstrates the efficacy of hot press forging as a dependable technique for the production of aluminium-graphite composites, resulting in enhanced physical and structural characteristics.